Implementation Health Insurance for Participants Receiving Contribution Assistance - Zulhijatur Rahmi; Nurlaila Nurlaila; Patmawati Patmawati; Miftahul Jannah; Widad Nurbariyyah (Journal of Islamic Economics and Finance Studies, 2026)
The main problem examined in this study concerns how the implementation of health insurance services for participants of BPJS Health, specifically those categorized as recipients of contribution assistance (PBI), is carried out in a Regional General Hospital (RSUD). This research applies a combination of approaches, including field research to gather primary data directly from the hospital setting, as well as a theoretical or library research approach to support the analysis with relevant academic sources. In addition, a statutory approach is used to review applicable laws and regulations related to health insurance services. The selection of informants in this study was conducted using a purposive sampling technique, ensuring that participants chosen were considered knowledgeable and relevant to the research objectives. To address the research problem, qualitative descriptive data analysis was employed to interpret and present findings systematically. The results indicate that, according to medical record officers, the implementation of BPJS Health services for PBI participants has been carried out in accordance with established standard operating procedures (SOP). However, this perspective differs from that of PBI patients, who report that the services they receive are still not optimal in practice.